The Role of Fibrin Monomer Compared to D-dimer and CRP in Determining COVID-19 Severity - Iriani, Anggraini; Sukorini, Usi; Fatina, Marsya Kaila; Aflah, Naja F; Aiman, Sarah A; Gemilang, Rizka K; Kamelia, Telly (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
Fibrin Monomer (FM), as a product of thrombin activity in cleaving fibrinogen, can be used as an early marker of thrombotic events in COVID-19 patients. D-dimer is a commonly used marker of hemostasis as a product of plasmin activity in cleaving polymeric fibrin. D-dimer is often used to help decide whether to initiate anticoagulant administration. This study aims to know whether FM can be used as a marker for thrombotic events such as D-dimer in COVID-19 patients; CRP levels were also examined to determine how inflammation affected the two hemostatic indicators. A total of 93 patients were confirmed with COVID-19 by PCR. The median (min-max) FM in the severe stage was 4.53 (2.26-58.20)ug/mL, whereas, in the mild-moderate stage, it was 4.21 (2.19-32.35 ug/mL. There are significant differences in median D-dimer levels in severe stages to mild-moderate, respectively 0.46 (0.14–7.58) and 0.7890, and ages. The level of FM that can be used to differentiate the severe stage is > 4.46 ug/mL (sensitivity 56.3%, specificity 58.0%) as in the D-dimer level is > 0.58 ug/mL ((sensitivity 75.0%, specificity 65.2%). There is a moderate positive correlation between fibrin monomer and D-dimer, a weak positive correlation between D-dimer and CRP, and no correlation between FM and CRP. This study concludes that the FM median level is higher in severe COVID-19 than in D-dimer. Fibrin monomer levels have a positive correlation with D-dimer. Fibrin Monomer levels are not affected by CRP.